1991
DOI: 10.1126/science.1846706
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Hepatocyte Growth Factor Receptor As the c- met Proto-Oncogene Product

Abstract: Hepatocyte growth factor (HGF) is a plasminogen-like protein thought to be a humoral mediator of liver regeneration. A 145-kilodalton tyrosyl phosphoprotein observed in rapid response to HGF treatment of intact target cells was identified by immunoblot analysis as the beta subunit of the c-met proto-oncogene product, a membrane-spanning tyrosine kinase. Covalent cross-linking of 125I-labeled ligand to cellular proteins of appropriate size that were recognized by antibodies to c-met directly established the c-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
1,226
2
12

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,135 publications
(1,265 citation statements)
references
References 24 publications
11
1,226
2
12
Order By: Relevance
“…Earlier studies have ®rmly established a role for both receptor (Baserga, 1994;Bottaro et al, 1991;D'Ambrosio et al, 1995;Khazaie et al, 1993) and non-receptor family tyrosine kinases (Egan et al, 1987a,b;Greenberg et al, 1989) in the transformation of normal cells. In particular, the product of the human src proto-oncogene, c-Src, has been implicated in the progression of colon cancer (Garcia et al, 1991;Cartwright et al, 1989Cartwright et al, , 1990Talamonti et al, 1991;Termuhlen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have ®rmly established a role for both receptor (Baserga, 1994;Bottaro et al, 1991;D'Ambrosio et al, 1995;Khazaie et al, 1993) and non-receptor family tyrosine kinases (Egan et al, 1987a,b;Greenberg et al, 1989) in the transformation of normal cells. In particular, the product of the human src proto-oncogene, c-Src, has been implicated in the progression of colon cancer (Garcia et al, 1991;Cartwright et al, 1989Cartwright et al, , 1990Talamonti et al, 1991;Termuhlen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This is triggered by extracellular stimuli that regulate the activity of several transcription factors that, in turn, modulate the expression of a number of proteins, ranging from cytoskeletal and cell-cell junctional components to cell cycle regulators and anti-apoptotic effectors 9, 10 . One major environmental inducer of invasive growth is hepatocyte growth factor (HGF, also known as scatter factor), the ligand for the MET tyrosine kinase receptor (also known as the HGF receptor) 11,12,13,14,15,16,17,18,19,20 (Box 1). MET function is required for various morphogenetic events in both embryonic and adult life 21,22 and it drives the malignant progression of several different types of tumours 23 .…”
mentioning
confidence: 99%
“…6,8 Isolation and culture of human peritoneal mesothelial cells Peritoneal mesothelial cells were obtained from resected tissue specimens of the greater omentum from patients who had undergone a laparotomy for an early gastric cancer. Informed consent was obtained from the surgical patients before surgery.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] Many types of malignant cells, mainly adenocarcinomas, are responsive to HGF, which stimulates cell proliferation, invasion and metastasis through an association with its receptor c-met product (HGFR). [8][9][10] We previously reported that HGF induced invasion of human gallbladder cancer cells into collagen gel and matrigelt, and such induction was neutralized by an antibody against HGF. Interestingly, HGF is produced by such nonepithelial stromal cells as fibroblasts 11,12 or endothelial cells, 13 and this production was also stimulated by some cancer-producing cytokines of IL-1, PDGF or bFGF.…”
mentioning
confidence: 99%